A multi-center investigation of breast-conserving surgery based on data from the Chinese Society of Breast Surgery (CSBrS-005) - Yu, Li-Xiang (Chin Med J (Engl), 2020)
BACKGROUND: Although breast-conserving surgery is one of the standard treatments for breast cancer, few studies have assessed its recent implementation in China. We aimed to clarify the current real-world status of breast-conserving surgery in China. METHODS: This cross-sectional survey relied on data collected by the Chinese Society of Breast Surgery (CSBrS) to examine patients who underwent this surgery between January 2018 and December 2018. The survey was conducted using a uniform electronic questionnaire to collect information, including clinical and pathological data on these patients. RESULTS: Overall, 4459 breast-conserving surgeries were performed in 34 member units of CSBrS, accounting for 14.6% of all breast cancer surgeries performed in these units during the study period. In patients who underwent breast-conserving surgery with information on tumor size available, more than half (61.2%) of the tumors were smaller than 2 cm in diameter, and only 87 (3.2%) tumors were larger than 4 cm in diameter. Among patients who underwent breast-conserving surgeries, 457 (10.2%) patients received neoadjuvant therapy before the surgery. Among patients with a reported margin width, 34 (2.0%) patients had a margin of ≤2 mm, and 1530 (88.2%) of them had a margin of >5 mm. CONCLUSIONS: This study demonstrated the rates of breast-conserving surgery in member units of the CSBrS, and introduced the characteristics and surgical margins of patients who underwent this surgery. This information helps describe the real-world status of breast-conserving surgery in China. TRIAL REGISTRATION: chictr.org.cn, ChiCTR1900026841; http://www.chictr.org.cn/showproj.aspx?proj=42783